2008
DOI: 10.21236/ada500672
|View full text |Cite
|
Sign up to set email alerts
|

Baiting Inside Attackers using Decoy Documents

Abstract: Abstract-The insider threat remains one of the most vexing problems in computer security. A number of approaches have been proposed to detect nefarious insider actions including user modeling and profiling techniques, policy and access enforcement techniques, and misuse detection. In this work we propose trap-based defense mechanisms and a deployment platform for addressing the problem of insiders attempting to exfiltrate and use sensitive information. The goal is to confuse and confound an adversary requiring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 3 publications
0
35
0
Order By: Relevance
“…Indeed, an APT aims to take control of a legitimate host inside of an organization, and the attacker will try to emulate normal behavior in order to avoid detection. However, an important difference is that an insider may not need to exfiltrate the data through a network, hence many approaches of insider threat detection focus on host-based logs [36] and honeypot strategies [37] instead of analyzing network traffic as it is done in our approach. An important observation is that the framework proposed in this paper could be easily integrated in insider threat detection systems: its approach based on traffic analyses can contribute significantly to existing insider threat solutions, although insider threat detection is not its primary objective.…”
Section: Insider Threatmentioning
confidence: 99%
“…Indeed, an APT aims to take control of a legitimate host inside of an organization, and the attacker will try to emulate normal behavior in order to avoid detection. However, an important difference is that an insider may not need to exfiltrate the data through a network, hence many approaches of insider threat detection focus on host-based logs [36] and honeypot strategies [37] instead of analyzing network traffic as it is done in our approach. An important observation is that the framework proposed in this paper could be easily integrated in insider threat detection systems: its approach based on traffic analyses can contribute significantly to existing insider threat solutions, although insider threat detection is not its primary objective.…”
Section: Insider Threatmentioning
confidence: 99%
“…On the data level we find solutions such as the honeywords and honeydocuments. The honeyword method [1] hides the password of a user between k hash values of random passwords, and honeydocuments [6] is again a trapbased mechanism which uses decoy documents. All these mechanisms serve as a safeguard against adversaries who try to get unauthorized data access.…”
Section: Biometric Templates As Honey Objectsmentioning
confidence: 99%
“…Our first test to this regard is between the plain feature vectors c tst and the protected templates ST of user i. The general mathematical formula we have used is: (6) where var (x) is the variance of the vector x, and it is interpreted as the covariance of x with itself. The covariance cov(x, y) between vectors x and y shows how much the two vectors differ from each other.…”
Section: Correlation Test Between Plain Feature Vectors and Protectedmentioning
confidence: 99%
“…Bowen et al [10] suggested using decoy documents to require an attacker to distinguish real information from false information, thereby confusing the attacker; this also allows the defenders to monitor those decoys, and hence the actions of the attackers. Ben Salem and Stolfo [7] characterize the desirable properties of decoys they have found effective.…”
Section: Deception and Floodingmentioning
confidence: 99%